Creative industries in China: art, design and media - Keane, Michael (Wiley (Polity Press), 2013)
Creative industries in China provides a fresh account of China’s emerging commercial cultural sector. The author shows how developments in Chinese art, design and media industries are reflected in policy, in market activity, and grassroots participation. Never has the attraction of being a media producer, an artist, or a designer in China been so enticing. National and regional governments offer financial incentives; consumption of cultural goods and services have increased; creative workers from Europe, North America and Asia are moving to Chinese cities; culture is increasingly positioned as a pillar industry. But what does this mean for our understanding of Chinese society? Can culture be industrialised following the low-cost model of China’s manufacturing economy. Is the national government really committed to social liberalisation? This engaging book is a valuable resource for students and scholars interested in social change in China. It draws on leading Chinese scholarship together with insights from global media studies, economic geography and cultural studies.